Strategi Self Reward dalam Meningkatkan Prestasi Belajar Siswa Tingkat Sekolah Menengah Atas - Aftian Nur Oktavia; Desy Safitri; Sujarwo (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Self-reward is used as a sign of appreciation and reward for individuals for the efforts that have been passed before. High school kids' self-rewarding can play a significant part in piquing their interest in learning. Giving appreciation to oneself or doing self-reward needs to be done by some students because by doing self-reward students can give appreciation for the endeavors undertaken and feel happy to be able to maintain mental health. This research uses the literature review research method. This study adopts a qualitative methodology, as well as the methods for data analysis used are those that include content analysis. This research is also used in three actions: data gathering, reducing, presenting, and making conclusions. This investigation concludes that the use of the self-reward strategy is important for students to develop learning achievement. Additionally, self-reward can foster learning motivation among students.